Matrix metalloproteinases in keratoconus – Too much of a good thing?. (May 2019) - di Martino, Erica; Ali, Manir; Inglehearn, Chris F.
Abstract: Keratoconus (KC) is a progressive, early onset, and often bilateral eye condition, in which the cornea gradually weakens and bulges out, and in advanced cases may eventually become cone-shaped. The available evidence suggests that it is a multifactorial disease with environmental and genetic contributions. Matrix Metalloproteinases (MMPs) are a family of 24 zinc-dependent proteases with the ability to degrade collagen and other extracellular matrix (ECM) proteins, which are important components of the cornea. During the past two decades a growing body of literature has accumulated suggesting a link between MMPs and keratoconus. This article aims to summarize the current knowledge on the role of MMPs in the pathogenesis of KC. MMP-driven ECM remodelling is thought to be a necessary step for cornea healing, but a fine balance in the expression of MMPs is essential in maintaining the integrity and transparency of the cornea and for its correct healing, and an imbalance in this tightly regulated process may, in the long term, result in the progressive weakening of the cornea. There is extensive evidence that MMPs are upregulated in the corneal tissue and tears of KC patients, implicating dysregulated proteolysis in KC, with an increase in the level of some MMPs, particularly MMP-1 and MMP-9, confirmed in multiple independent studies. There is also evidence for a causative link between inflammation, which could result from the mechanical trauma due to contact lens wearing or/and eye rubbing, and the increased MMPs production observed in KC. However, the precise role of each MMP in the cornea is still unclear and the mechanisms causing their upregulation are mostly undiscovered. Further studies are required to verify the functional role of specific MMPs in KC development and assess the genetic association between common MMPs variants and risk of KC. As MMPs inhibitors are in development, this information could potentially drive the discovery of new treatments for KC. Highlights: Keratoconus (KC) is a corneal disease with environmental and genetic causes. Matrix Metalloproteinases (MMPs) contribute to corneal integrity and healing. Increased levels of some MMPs, particularly MMP-1 and MMP-9, are found in KC. Dysregulation of MMPs may contribute to corneal weakening in KC. Further studies in this area may drive the discovery of new treatments for KC.